A comparative study on reduced complexity 2-D detectors for bit patterned media - Myint, Lin M.M.; Supnithi, Pornchai (My University, 2011)
In this paper, we compare the performance of the reduced complexity 2-D detection methods: Graph-based detection and Viterbi-based detection for the 2-D interference bit patterned media channels at various areal densities. In the graph-based detection, the complexity is reduced by ignoring the ITI from the cornered islands in designing the factor graph. In Viterbi-based detector, a trellis for the ISI only is considered. However, both methods improve the ITI mitigation with the help of multi-track processing and iterative processing. Between them, the graph-based detection needs higher computational complexity than the Viterbi-based detection. However, the graph-based detection method provides a significant performance gain over the Viterbi-based detect.on © 2011 IEEE.
Keywords: Bit patterned media (BPM); graph-based detector; inter-track interference; multi-track detection; Viterbi detector